2017
DOI: 10.1080/00986445.2017.1384921
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and thermo-oxidative stability and kinetics of decomposition of PHBV/sisal composites

Abstract: The decomposition behaviours of composites made of poly(3-hydroxybutyrate-co-3hydroxyvalerate) (PHBV) and sisal were assessed in terms of thermal stability and decomposition kinetics, under inert and oxidative conditions, by means of multi-rate linear non-isothermal thermogravimetric experiments. A Statistical Design of Experiments was applied to study the influence of the addition of sisal (0 %wt-30 %wt), the presence coupling agent (Yes/No) and the applied conditions of work (inert or oxidative). An improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…A previous thermogravimetric analysis [30,31] showed that the trigger of decomposition happened far above their melting point, which ensured a good performance of the composites at high processing temperatures. Figure 9 shows the calorimetric analysis of the samples submitted to recycling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous thermogravimetric analysis [30,31] showed that the trigger of decomposition happened far above their melting point, which ensured a good performance of the composites at high processing temperatures. Figure 9 shows the calorimetric analysis of the samples submitted to recycling.…”
Section: Resultsmentioning
confidence: 99%
“…The study of the thermal decomposition of materials stands out as the main basis for the correct tuning of facilities for energy recovery purposes. In this sense, PLA/sisal and PHBV/sisal have proved their suitable behaviour for thermal recycling [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) was applied to assess the thermal decomposition profiles as previously described for persimmon [31], apple tree residues [32] or biopolymers [33]. Experiments were carried out in a Mettler Toledo TGA/SDTA 851 (Columbus, OH, USA).…”
Section: Characterization and Pre-treatment Of Rice Strawmentioning
confidence: 99%
“…Rice straw, for example, is usually eliminated by uncontrolled burning with harmful consequences related to air, flora, and fauna pollution in wetlands. As an alternative, rice waste is abandoned or sunk, being decomposed in fields, causing major die-off of fish and other aquatic fauna in deeper areas [2]. Currently, different European moratoria permitting uncontrolled burning are being applied, since no reliable solutions are being implemented.…”
Section: Introductionmentioning
confidence: 99%